Pengaruh Permainan Tradisional Balap Karung Terhadap Perilaku Prososial Anak Usia 5-6 Tahun di TK Aster Kelurahan Molosipat W Kecamatan Kota Barat Kota Gorontalo - Indar Yabu; Pupung Puspa Ardini; Icam Sutisna (Institut Nalanda, 2024)
Indar Yabu. 2024. The Effect of Traditional Sack Race Games on Prosocial Behavior of Children Aged 5-6 Years at TK Aster Kindergarten, Molosipat W Subdistrict, Kota Barat District, Gorontalo City. Early Childhood Education Teacher Program, Faculty of Education. Principal Supervisor: Dr. Pupung Puspa Ardini, S.Pd., M.Pd., MCE, and Co-Supervisor: Icam Sutisna, S.Pd., M.Pd. Early childhood education institutions can foster prosocial behavior in children through traditional sack race games, which stimulate various aspects of children's growth and development. This study aims to determine the effect of traditional sack race games on the prosocial behavior of children aged 5-6 years at TK Aster Kindergarten, Molosipat W Subdistrict, Kota Barat District, Gorontalo City. This research employed a quantitative approach with an experimental method (one group pretest-posttest design) and included a sample of 15 children. The results indicated that the significance value (2-tailed) is 0.000 < 0.05, meaning H0 is rejected, and H1 is accepted, showing a significant difference in children's prosocial behavior after participating in the sack race game. Therefore, it can be concluded that traditional sack race games positively influence the prosocial behavior of children aged 5-6 years.